Nonvascular Nervous System Complications in Pediatric Patients with COVID-19 Infection - Palabiyik, Figen; Koral, Korgün; Pruthi, Sumit (Journal of Pediatric Neurology, 2022)
Coronavirus disease (COVID-19) is caused by a novel severe acute respiratory syndrome coronavirus 2 virus which primarily targets the lungs. However, the central nervous system (CNS) and peripheral nervous system involvement due to COVID-19, however, has been reported as early as the cases of respiratory system involvement. In addition, there have been many reports describing neuroimaging features of COVID-19, but data beyond case studies in the pediatric population are still limited, indicating limited CNS involvement. The CNS involvement and complications include, but are not limited to, encephalopathy, meningoencephalitis, ischemic stroke, venous sinus thrombosis, acute necrotizing encephalopathy, acute disseminated encephalomyelitis, posterior reversible encephalopathy syndrome, acute cerebellitis, acute hemorrhagic myelitis, and Guillain–Barré syndrome. In this manuscript, we will discuss the imaging characteristics of some of these entities with a known diagnosis of COVID-19.
Keywords: COVID-19; central nervous system; peripheral nervous system